Complex ALK Fusions Are Associated With Better Prognosis in Advanced Non-Small Cell Lung Cancer - Kang, Jin; Zhang, Xu-Chao; Chen, Hua-Jun; Zhong, Wen-Zhao; Xu, Yang; Su, Jian; Zhou, Qing; Tu, Hai-Yan; Wang, Zhen; Xu, Chong-Rui; Yang, Xue-Ning; Chen, Zhi-Hong; et al. (Frontiers in Oncology, 2020)
Background Echinoderm microtubule-associated protein-like 4 (EML4) is the canonical anaplastic lymphoma kinase (ALK) fusion partner in non-small cell lung cancer (NSCLC), and ALK-positive patients showed promising responses to ALK tyrosine kinase inhibitors (TKIs). However, studies that comprehensively investigate ALK TKI treatment in patients with different ALK fusion patterns are still lacking. Methods Ninety-eight ALK-positive patients with advanced NSCLC were retrospectively studied for their response to crizotinib and subsequent treatments. Comprehensive genomic profiling (CGP) was conducted to divide patients into different groups based on their ALK fusion patterns. Non-canonical ALK fusions were validated using RNA-sequencing. Results 54.1% of patients had pure canonical EML4-ALK fusions, 19.4% carried only non-canonical ALK fusions, and 26.5% harbored complex ALK fusions with coexisting canonical and non-canonical ALK fusions. The objective response rate and median progression-free survival to crizotinib treatment tended to be better in the complex ALK fusion group. Notably, patients with complex ALK fusions had significantly improved overall survival after crizotinib treatment (p = 0.012), especially when compared with the pure canonical EML4-ALK fusion group (p = 0.010). The complex ALK fusion group also tended to respond better to next-generation ALK TKIs, which were used as later-line therapies. Most identified non-canonical ALK fusions were likely to be expressed in tumors, and some of them formed canonical EML4-ALK transcripts during mRNA maturation. Conclusion Our results suggest NSCLC patients with complex ALK fusions could potentially have better treatment outcomes to ALK TKIs therapy. Also, diagnosis using CGP is of great value to identify novel ALK fusions and predict prognosis.